2017
DOI: 10.21037/qims.2017.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal cranial sonography: ultrasound findings in neonatal meningitis—a pictorial review

Abstract: Neonatal bacterial meningitis is a common manifestation of late onset neonatal sepsis. Cranial sonography (CRS) has a crucial role in assessment of infants with clinical suspicion of bacterial meningitis as well as follows up of its complications. CRS is performed with high frequency transducer through anterior fontanelle in both coronal and sagittal planes. Various sonographic findings range from echogenic and widened sulci, ventriculomegaly, ventriculitis, hydrocephalus, extra-axial fluid collections, cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 14 publications
1
25
0
2
Order By: Relevance
“…Cranial sonography is also beneficial in the diagnosis of various neonatal pathologies other than hydrocephalus. 13 MRI is the best diagnostic and prognostic modality but availability and cost are the major concerns over it. CT scan exposes patients to a high dose of radiations, so a low dose protocol may be a suitable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Cranial sonography is also beneficial in the diagnosis of various neonatal pathologies other than hydrocephalus. 13 MRI is the best diagnostic and prognostic modality but availability and cost are the major concerns over it. CT scan exposes patients to a high dose of radiations, so a low dose protocol may be a suitable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…12 Most of these deaths occurred in developing and under developed countries and leading cause of deaths include pneumonia, meningitis and sepsis. 13 Neonatal meningitis is inflammation of arachnoid and pia mater.…”
Section: Discussionmentioning
confidence: 99%
“…Meningitis is common presentation of LOS, 11 and it results in serious neurological sequale and 12 In a study conducted in India showed the prevalence of meningitis as 22.5% in neonates with LOS. 10 To the best of my knowledge, there is little information in Pakistan regarding the relation of meningitis with LOS in neonates.…”
mentioning
confidence: 99%
“…Neonatal meningitis (NM) represents an inflammatory response to many types of cerebrospinal fluid (CSF) and pia-arachnoid infections of the central nervous system (CNS). NM can be classified as early or late depending of their occurrence by vertical transmission during the first week of life, or by interpersonal/nosocomial transmission as a late onset presentation of neonatal sepsis (1,2). Grampositive NM represents the majority of cases, with Group B streptococcus (GBS) as the leading causative pathogen in this class (3).…”
Section: Introductionmentioning
confidence: 99%
“…Very often the clinical course of NM is characterized by sudden worsening, usually caused by convulsive states, but at times associated with cerebrovascular complications and cerebral strokes. Clinically it can be challenging to evaluate the severity, exact location, and degree of insult to the brain; for this reason, an immediate radiological recognition of these pathological patterns in patients admitted to Neurointensive Care Units (NICU) is pivotal in providing clinicians with useful information to guide the medical treatments (2).…”
Section: Introductionmentioning
confidence: 99%